1996
DOI: 10.1111/j.1600-0897.1996.tb00010.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte Subsets and Mitogen Stimulation of Blood Lymphocytes in Normal Pregnancy

Abstract: During normal pregnancy, a state of systemic suppression of the maternal immune system seems to be present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
3
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 50 publications
7
43
3
3
Order By: Relevance
“…The lack of increase in this population in the blood of GDM-or Type 2 diabetes-afflicted women indicates an increase in immune activation versus immunosuppression during late pregnancy in diabetic patients and may in turn correlate with a greater risk to the pregnancy. A higher number of CD4+CD29+ (presumed helper/inducer cells) activated T cell subpopulations were also observed in GDM patients than in the blood of women experiencing a normal pregnancy, and a previous investigation showed this population to be down-regulated in normal pregnancy (35). These observations suggest that maternal immunosuppression, which is normally increased during pregnancy to compensate for the immunostimulatory activity of paternal antigens, may not be as effective in GDM patients as in healthy women.…”
Section: Lymphocyte Activationmentioning
confidence: 60%
“…The lack of increase in this population in the blood of GDM-or Type 2 diabetes-afflicted women indicates an increase in immune activation versus immunosuppression during late pregnancy in diabetic patients and may in turn correlate with a greater risk to the pregnancy. A higher number of CD4+CD29+ (presumed helper/inducer cells) activated T cell subpopulations were also observed in GDM patients than in the blood of women experiencing a normal pregnancy, and a previous investigation showed this population to be down-regulated in normal pregnancy (35). These observations suggest that maternal immunosuppression, which is normally increased during pregnancy to compensate for the immunostimulatory activity of paternal antigens, may not be as effective in GDM patients as in healthy women.…”
Section: Lymphocyte Activationmentioning
confidence: 60%
“…This does not reflect methodological errors, since the same methodology and the same markers proved to be able to define suppressive lymphocyte phenotypes during normal pregnancy (30) and in patients with GuillainBarré syndrome (5) and active phenotypes in patients with recurrent spontaneous abortions (17), polyneuropathy associated with monoclonal gammopathy (35), multiple sclerosis (36), and preeclampsia (31). Thus, the results of the present study support the notion that the effects of photopheresis should also be investigated by determination of functional properties like cytokine secretion patterns (20) as well as dendritic cell function and dendritic cell-T cell interactions (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Kaskura (19) showed that human pregnancy serum suppresses the reactivity of mixed leukocyte cultures; the inhibitory effect reached its maximum during late pregnancy and disappeared shortly after delivery. T cell proliferation in response to mitogens is also inhibited in the presence of pregnancy sera (20). This led to the evaluation of inhibitory properties of the many known pregnancy-related hormones and factors.…”
Section: Discussionmentioning
confidence: 99%